Rehabilitation Belief and Engagement Transformation (RBET) Model: A Grounded Theory Approach - Cuambot, Jade Ibhar V.; Reyes, Marc Eric S.; Trinidad, Karen Katrina V. (Makara Human Behavior Studies in Asia, 2026)
Competitive sports injuries have significant physiological and psychological consequences for athletes. While rehabilitation medicine effectively addresses the physical aspects of injury recovery, the psychological and emotional journey of injured athletes remains neglected. Thus, the current study addresses this gap by examining athletes’ transforming belief systems and emotional experiences during injury rehabilitation. A qualitative research design grounded in grounded theory principles was conducted with professional athletes to understand how their beliefs toward rehabilitation evolved over time. Findings revealed a dynamic process of belief transformation consisting of seven interconnected stages, captured in the Rehabilitation Belief and Engagement Transformation (RBET) Model: (1) Pre-rehabilitation Beliefs and Practices, (2) Initial/Early Emotional and Mental Struggles, (3) Emergence of Motivational Drivers, (4) Engagement in Rehabilitation, (5) Gradual Recovery and Readjustment, (6) Re-evaluation and Turning Point, and (7) Reintegration and Performance Adaptation. This seven-step model traces athletes’ journey from initial skepticism and risk-taking behaviors to emotional struggles marked by distress, fear, and self-doubt. With the emergence of motivational drivers, athletes gradually engage in rehabilitation to navigate both physical and psychological challenges. Rehabilitation progress fosters emotional upheaval and cognitive shifts, leading to re-evaluation of beliefs and full adherence to recovery procedures. Ultimately, athletes reintegrate into sport with adjusted mindsets, strategic performance adaptations, and renewed identity. The RBET model contributes to a more holistic understanding of recovery, emphasizing that effective rehabilitation must address not only physiological healing but also the psychological and emotional transformations that athletes undergo.